2019
DOI: 10.5935/0004-2749.20190021
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the aqueous humor total antioxidant capacity, total oxidant status, and levels of IL-6 and VEGF with diabetic retinopathy status

Abstract: We aimed to compare the aqueous humor total oxidant status, total antioxidant capacity, and levels of interleukin-6 and vascular endothelial growth factor between patients with diabetic retinopathy and controls and to correlate these levels with the DR status. Methods: Patients who underwent cataract surgery were enrolled. The first group (control group) comprised patients without diabetes; the second group comprised diabetic patients without retinopathy; the third group comprised patients with nonproliferativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
1
6
0
3
Order By: Relevance
“…15 Bozkurt et al reported similar results in an aqueous study. 19 Similarly, in this study, there was no difference of TAS in group-2 and group-3. However, in patients with DME with HRN (group-1), TAS was statistically significantly higher than isolated DM patients (group-3).…”
Section: Discussionsupporting
confidence: 51%
“…15 Bozkurt et al reported similar results in an aqueous study. 19 Similarly, in this study, there was no difference of TAS in group-2 and group-3. However, in patients with DME with HRN (group-1), TAS was statistically significantly higher than isolated DM patients (group-3).…”
Section: Discussionsupporting
confidence: 51%
“…Exclusion criteria included glaucoma, diabetic retinopathy, infectious ocular diseases, shallow anterior chamber, branch retinal vein occlusion, pterygium, Sjogren's disease, corneal transplant status, and postoperation status. These underlying ocular diseases and conditions were considered to either influence TAC or interfere with ECD measurement 11‐15 . A flow diagram for subject recruitment is presented in Supporting Information Figure S1.…”
Section: Methodsmentioning
confidence: 99%
“…Diseases such as glaucoma, diabetic retinopathy, infectious ocular diseases, shallow anterior chamber, branch retinal vein occlusion, pterygium, and Sjogren's disease may all lead to increased oxidative stress and subsequent dysfunction among CEC. [11][12][13][14][15][16] It should also be noted that ocular surgery, especially cataract surgery, is an important risk factor for CEC loss and subsequent corneal blindness. 17 For this reason, preoperative ECD evaluation is important and recommended.…”
Section: Undesirable Ecd Declinementioning
confidence: 99%
See 1 more Smart Citation
“…Model: -our extremely next neighbor 'The Mars' we can see the strong evidence of presence of water on that planet yet been a littler planet when contrasted with the Earth it cools quicker, its center quits moving bringing about the loss of the planets attractive field. When the attractive shield vanishes, the sun based breezes makes the water to bubble lastly dissipates into the space leaving the planet a dead bundle of residue [3]. The equivalent can be the situation with our space make.…”
Section: The Detailed Descriptionmentioning
confidence: 99%